Állami kitüntetések az ellenforradalom leverésében résztvevőknek, törvényerejű rendelet a Magyar Testnevelés és Sport Tanács létrehozásáról . State Awards for Persons Helping Crush the Counter-Revolution, Decree on Setting up the Physical Training Council - Héderváry, Claire de (1958)
Records of this digital collection were assembled to document the work of the UN Special Committee on the Problem of Hungary established on January 10, 1957 by the United Nations General Assembly for the purpose of investigating the 1956 Hungarian revolution. Principal contributor(s): Magyar Közlöny